The clinical and pathological features of 133 colorectal cancer patients with brain metastasis: a multicenter retrospective analysis of the Gastrointestinal Tumors Working Committee of the Turkish Oncology Group (TOG) - (:unkn) unknown (HUMANA PRESS INC, 2014)
Brain metastasis in colorectal cancer is highly rare. In the present study, we aimed to determine the frequency of brain metastasis in colorectal cancer patients and to establish prognostic characteristics of colorectal cancer patients with brain metastasis. In this cross-sectional study, the medical files of colorectal cancer patients with brain metastases who were definitely diagnosed by histopathologically were retrospectively reviewed. Brain metastasis was detected in 2.7 % (n = 133) of 4,864 colorectal cancer patients. The majority of cases were male (53 %), older than 65 years (59 %), with rectum cancer (56 %), a poorly differentiated tumor (70 %); had adenocarcinoma histology (97 %), and metachronous metastasis (86 %); received chemotherapy at least once for metastatic disease before brain metastasis developed (72 %), had progression with lung metastasis before (51 %), and 26 % (n = 31) of patients with extracranial disease at time the diagnosis of brain metastasis had both lung and bone metastases. The mean follow-up duration was 51 months (range 5-92), and the mean survival was 25.8 months (95 % CI 20.4-29.3). Overall survival rates were 81 % in the first year, 42.3 % in the third year, and 15.7 % in the fifth year. In multiple variable analysis, the most important independent risk factor for overall survival was determined as the presence of lung metastasis (HR 1.43, 95 % CI 1.27-4.14; P = 0.012). Brain metastasis develops late in the period of colorectal cancer and prognosis in these patients is poor. However, early screening of brain metastases in patients with lung metastasis may improve survival outcomes with new treatment modalities.
Keywords: Colorectal cancer; Brain metastasis; Prognosis; PARTITIONING ANALYSIS RPA; PROGNOSTIC-FACTORS; CARCINOMA; SURVIVAL; RADIOSURGERY